Análisis fotográfico: Publicidades de las pequeñas y medianas empresas de la ciudad de Babahoyo - Jimenez Troya, Geanella Maytee (2020)
This case study specifically shows theoretical and field research on the influence of photographs in the advertising of small and medium-sized companies in the city of Babahoyo, with the objective of knowing the advantages and disadvantages that an image could have In relation to its advertising, the descriptive method will also be considered based on interviews aimed at small and medium-sized companies that are most recognized at the local level, as well as an observation sheet that recaptured the real situation of SMEs mental perspective. Finally, photos will be presented showing the type of advertising used by businesses and micro companies in the sector studied.